2013
DOI: 10.1155/2013/763191
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry in the Detection of Neonatal Sepsis

Abstract: Neonatal sepsis remains a burden problem by showing minimal initial symptoms of subtle character, nonspecific manifestation, and diagnostic pitfalls. The clinical course can be fulminant and fatal if treatment is not commenced promptly. It is therefore crucial to establish early diagnosis and initiate adequate therapy. Besides clinical symptoms, the most reliable laboratory markers in establishing diagnosis is currently the combined measurement of CRP and a cytokine (IL-6 and IL-8). Due to their different kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 58 publications
1
26
0
5
Order By: Relevance
“…Signs and symptoms suggestive of clinical sepsis have been described in detail in the previous studies [8], [11], [12]. As part of the evaluation, two or more of the following previously validated hematologic criteria were used as indicators for sepsis: (1) absolute neutrophil count of >12×10 3 cells/mm 3 , (2) white blood cell count of >20×10 3 cells/mm 3 , (3) immature/total neutrophil ratio of >20%, (4) platelet count of <150×10 3 cells/mm 3 , (5) CRP of >3.0 mg/L.…”
Section: Methodsmentioning
confidence: 83%
“…Signs and symptoms suggestive of clinical sepsis have been described in detail in the previous studies [8], [11], [12]. As part of the evaluation, two or more of the following previously validated hematologic criteria were used as indicators for sepsis: (1) absolute neutrophil count of >12×10 3 cells/mm 3 , (2) white blood cell count of >20×10 3 cells/mm 3 , (3) immature/total neutrophil ratio of >20%, (4) platelet count of <150×10 3 cells/mm 3 , (5) CRP of >3.0 mg/L.…”
Section: Methodsmentioning
confidence: 83%
“…Also, it can be incorporated as a valuable marker to exclude neonatal sepsis (NS) [9][10][11][12][13][14]. Studies have showed that the expression of CD64 on neutrophils has high sensitivity and accuracy in identifying sepsis [14][15][16]. However, diversities of CD64 expression descriptions and various cut-off values exist in different laboratories [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed, that in the early phase of inflammation, cytokine-induced leukocyte activation changes the expression of many adhesion molecules on the surface of granulocytes and monocytes. The best known adhesion molecules are CD11b, CD54, CD62L and CD64 [14,15,16]. Differences in assessment of the quantitative expression of adhesion molecules in healthy and infected neonates with varying degrees of gestational maturity have prompted us to carry out a study in a population of preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…Uważa się, że we wczesnej fazie zapalenia następuje aktywacja leukocytów indukowana cytokinami, co powoduje zmiany ekspresji wielu molekuł adhezyjnych na powierzchni granulocytów i monocytów. Do najlepiej poznanych należą CD11b, CD54, CD62L i CD64 [14,15,16]. Rozbieżności w ocenie ilościowej ekspresji molekuł adhezyjnych u zdrowych i chorych noworodków o różnym stopniu dojrzałości płodowej, skłoniły nas do przeprowadzenia badań własnych u wcześniaków.…”
Section: Introductionunclassified